Pengaruh Terapi Murotal Surah Ar-Rahman terhadap Tingkat Stres Akademik Mahasiswa Keperawatan - Febrianti, Tressia; Masdiana, Masdiana; Hawara, Gian (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2025)
People will encounter a variety of issues that can cause stress, particularly during the adolescent development stage. In fulfilling developmental tasks and various activities such as academic demands, campus activities, and interpersonal problems can make students experience various problems. High levels of stress, especially in college students, will have an impact on anxiety and depression, poor lifestyle, sleep pattern disorders, headaches, feelings of helplessness to suicidal behavior. Non- pharmacological treatment efforts to reduce stress levels include psychoreligious therapy, namely murrotal Al-Qur'an Surah Ar-Rahman. The purpose of this study was to determine the effect of murotal therapy surah Ar-Rahman on the academic stress level of nursing students of STIKes Raflesia. This type of research is quasi- experimental with a pre-post test control group design to compare the actions taken before and after the experiment. the sampling technique is using total sampling, with 15 students assigned to the intervention group and 15 students as the control group, the intervention group is given therapy for 3 days with a duration of 30 minutes. Univariate analysis in this study is presented in categorical form (frequency and presentation) and bivariate analysis using the Wilcoxon signed rank test statistical test with a degree of significance α = 0,05. The results of data analysis obtained a significant value of 0,005, there is an effect of giving murotal therapy Surah Ar-Rahman on the academic stress level of nursing students. Surah Ar- Rahman murotal therapy can be one of the Islamic therapeutic interventions that use Surah Al-Quran as a medium in reducing student academic stress.